2016
DOI: 10.1021/acs.molpharmaceut.5b00866
|View full text |Cite
|
Sign up to set email alerts
|

Predictable Heating and Positive MRI Contrast from a Mesoporous Silica-Coated Iron Oxide Nanoparticle

Abstract: Iron oxide nanoparticles have great potential as diagnostic and therapeutic agents in cancer and other diseases; however, biological aggregation severely limits their function in vivo. Aggregates can cause poor biodistribution, reduced heating capability, and can confound their visualization and quantification by magnetic resonance imaging (MRI). Herein, we demonstrate that the incorporation of a functionalized mesoporous silica shell can prevent aggregation and enable the practical use of high-heating, high-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 82 publications
5
103
0
Order By: Relevance
“…However, coating the IONPs with mesoporous silica has been shown to improve stability [152, 153]. Moreover, this coating has demonstrated a high stability within biological environments and has maintained that stability within CPAs [154, 155]. …”
Section: Bioengineering Applicationsmentioning
confidence: 99%
“…However, coating the IONPs with mesoporous silica has been shown to improve stability [152, 153]. Moreover, this coating has demonstrated a high stability within biological environments and has maintained that stability within CPAs [154, 155]. …”
Section: Bioengineering Applicationsmentioning
confidence: 99%
“…To induce particle stimulation, radio frequency and light may be used. However, aggregation with proteins or other solutes may occur [65], reducing the heat generation capacity of these systems. These effects can be reduced by coating the particles with silica or polypropylene glycol [66].…”
Section: Future Trends In Otcmentioning
confidence: 99%
“…Regarding MRI/MRT used in PCa related NP settings the number of publications is constantly increasing [104,339,340,341,342,343,344]. Jin et al, for example, evaluated MRI-guided focal NP-based (porphysomes) photothermal therapy (see below) in an orthotropic PCa mouse model, and concluded that it might be an effective and safe technique to treat PCa, with a low risk of progression of disease [343].…”
Section: Multimodal Imaging Options For Prostate and Breast Cancermentioning
confidence: 99%